2002
DOI: 10.1038/sj.leu.2402471
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic transformation of CD52pos to CD52neg leukemic T cells as a mechanism for resistance to CAMPATH-1H

Abstract: Immunotherapy utilizing CAMPATH-1H for patients with chemotherapy-refractory chronic lymphocytic leukemia has yielded encouraging results with many reports of complete remission. Here we report the outcome of two patients with CD4-positive T cell prolymphocytic leukemia treated with CAM-PATH-1H. Both patients responded rapidly to treatment and subsequently developed CD4 lymphopenia. One patient remained in complete remission after 14 weeks of treatment. Serial peripheral blood flow cytometry revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Loss of CD20 or CD52 antigen expression following immunotherapy with rituximab or alemtuzumab is common. 12,30,31 It is interesting that none of our patients were treated with rituximab or alemtuzumab during the follow-up period, and thus, these antigenic changes are not due to binding by therapeutic antibody to the assessed antigen. However, modulation of the antigen or antigenic deletion in response to other therapeutic approaches cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of CD20 or CD52 antigen expression following immunotherapy with rituximab or alemtuzumab is common. 12,30,31 It is interesting that none of our patients were treated with rituximab or alemtuzumab during the follow-up period, and thus, these antigenic changes are not due to binding by therapeutic antibody to the assessed antigen. However, modulation of the antigen or antigenic deletion in response to other therapeutic approaches cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The role of alemtuzumab in generating such a clonal expansion in our patient remains speculative, but, in agreement with this hypothesis, it has been shown that alemtuzumab cross-linking may result in T-cell activation in vitro 38,39 and that alemtuzumab may promote the expansion of CD52 Ϫ T-cell clones in vivo. [40][41][42] On the other hand, the expansion of nonmalignant T-cell clones may be unrelated to the disease or the treatment because expanded T-cell clones can be detected by molecular studies in the blood of patients, especially elderly patients, with benign dermatoses or non-CTCL malignant diseases. 27 Identifying one or several common antigen(s) specific to malignant Sézary cells, which may trigger or promote the proliferation of the malignant clone, would represent significant progress in the understanding of the pathogenesis of SS.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of disease acceleration (e.g., CML blast crisis) or transformation (e.g., diffuse large B cell lymphoma in low grade lymphoma or CLL) (66, 74, 96, 171, 172). Prognostication, especially in CLL, with detection of ZAP70 or CD38 (135, 136, 173–179), acute leukemia (59, 77, 78, 180–185), or myeloma, whereby phenotype, presence of circulating plasma cells, or assessment of proliferation rate can predict progression (111, 114, 186–188). …”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%